Comparative study of ProSeal laryngeal mask airway and endotracheal tube in patients undergoing laparoscopic surgeries under general anaesthesia - Shibin, Afra; Priyamkari, Amrutha; A. A., Habib Rahaman (International Journal of Research in Medical Sciences, 2022)
Background: Supra glottic airway devices (SGAD) is integral to airway management during general anesthesia. PLMA, a second-generation SGAD with a gastric channel and an efficient seal, is an alternative for the COETT, which is the gold standard for securing the airway. SGAD has the advantage of lesser hemodynamic changes during insertion and removal. This study aimed to compare the hemodynamic and ventilatory changes between PLMA and the endotracheal tube (ETT). Methods: Prospective randomized study, conducted at Yenepoya medical college hospital on 90 patients undergoing elective laparoscopic surgeries under general Anaesthesia. The patients were divided into groups; group p=45 patients (PMLA) and E=45 patients (COETT). Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), peripheral oxygen saturation (SpO2) and end-tidal carbon dioxide (EtCO2) were documented at baseline, at 1, 3, 5 and 8 minutes after placement of airway device. Results: Differences in vital parameters at baseline were statistically insignificant. HR, SBP, DBP and MAP were significantly higher in group E compared to group P at 1st, 3rd, 5th and 8 min after the insertion of the airway device. There was no statistically significant difference in SpO2 and EtCO2. Post-extubation laryngopharyngeal morbidity was noted in 5 patients with ETT compared to 1 patient with PMLA. Conclusions: PLMA provides better hemodynamic stability at insertion when compared to ETT. Both PLMA and ETT provide good oxygenation and ventilation during elective laparoscopic surgeries. Insertion at first attempt was more successful with PLMA when compared to ETT.